Dynamic Linkages of Carbon Emissions, Economic Growth, Energy Consumption, Tourism Indicators and Population: Evidence from Second-tier Cities in Thailand - Chanthawong, Anuman; Choibamroong, Therdchai (International Journal of Energy Economics and Policy, 2022)
Tourism is important and can generate economic growth for many countries, including Thailand. Since the government’s launch of the 55 Second-Tier Cities Tourism Destination Project, second-tier cities in Thailand have become tourist attractions. This study investigates linkages among carbon emissions, economic growth, tourism indicators, energy consumption and population in the 55 second-tier cities using annual data for the 2019-2017 period through panel dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS), the autoregressive distributed lag (ARDL) method, the generalized method of moments (GMM) and Granger causality testing. The results show that energy consumption, per capita gross provincial product, the number of domestic and international tourists and the population size directly influence the carbon emissions level. The policy implications for second-tier cities include 1) increasing energy efficiency, for instance by installing alternative energy such as solar, wind and biofuel energy; 2) promoting loans with special interest rates to assist tourism entrepreneurs in providing energy-efficient products; 3) boosting public awareness of energy efficiency, energy savings and environmental pollution; 4) providing special funds and business tax refunds for those who reduce carbon emissions; 5) proactively promoting low-carbon tourism activity among tourists; and 6) introducing and enforcing environmental taxes.